Analyzing Types of Mispronunciation “Deletion” 6 Grade in Elementary School - Ni Made Aprilia Suciani; Ni Made Verayanti Utami (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the types of phonological deletion errors found in the oral reading of sixth-grade students at SDN 11 Dauh Puri. The research is framed within David Odden’s (2013) theory of phonological processes, focusing on deletion as a common feature of mispronunciation. The data were collected from students reading a short English passage aloud, and errors were categorized into five types of deletion: function word deletion, unstressed vowel deletion, consonant cluster simplification, intervocalic consonant deletion, and word-final consonant deletion. The analysis revealed that function word deletion occurred most frequently (44.4%), followed by unstressed vowel deletion (22.2%). Each of the remaining types accounted for 11.1% of the total. These errors reflect students' tendency to simplify complex phonological structures, often influenced by their first language and limited exposure to natural spoken English. The study highlights the need for explicit pronunciation instruction that addresses connected speech features and helps learners build awareness of reduced forms in English